The expression tractability of biological traits shaped by natural selection. (20th August 2019) - Liu, Li; Wang, Jianguo; Yang, Jian-Rong; Wang, Feng; He, Xionglei
Abstract: Understanding how gene expression is translated to phenotype is central to modern molecular biology, and the success is contingent on the intrinsic tractability of the specific traits under examination. However, an a priori estimate of trait tractability from the perspective of gene expression is unavailable. Motivated by the concept of entropy in a thermodynamic system, we here propose such an estimate ( S T ) by gauging the number ( N ) of expression states that underlie the same trait abnormality, with large S T corresponding to large N . By analyzing over 200 yeast morphological traits, we show that S T predicts the tractability of an expression-trait relationship. We further show that S T is ultimately determined by natural selection, which builds co-regulated gene modules to minimize possible expression states.